The Impact of COVID-19 Pandemic and Earnings Management: Does the History of Managerial Ability Have a Role? - Karinea Hariadi; Ari Kristanto (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2022)
This research aims to analyze the early impact of the COVID-19 pandemic on the tendency of earnings management in Indonesia, with a history of managerial ability as a moderating variable. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Using the purposive sampling technique, as many as 126 companies can meet the research sample criteria. The data analysis technique used is Moderated Regression Analysis (MRA). The results show that the impact of the COVID-19 pandemic has a positive effect on earnings management tendencies in Indonesia. It can be interpreted that the higher the impact of the COVID-19 pandemic received by the company, the higher the earnings management behavior. However, this can be weakened by the history of managerial ability. Companies with a history of managerial ability can cope with the impact of the COVID-19 pandemic and are more considering improving their performance quality rather than carrying out earnings management, which risks reducing the company's value.